Perception of some intonational deviations in melodies - FYK, J. (Archives of Acoustics, 1994)
The aim of the experimental research was to determine sensitivity to intonational deviations in melodies. The following intervals were investigated: prime, minor second, major second, perfect, fourth, augmented fourth, diminished fifth and octave, as they appear in both tonal and atonal contexts. Subjects were music education students from Pedagogical University in Zielona Góra (Group One) and students from Chopin Academy of Music, Warsaw (Group Two). Each group consisted of 22 subjects. During each experimental trial the subjects listen to two versions of a short melody played on the piano. The second version of the melody was a transposition of the first one by a major second upwards. Moreover, in fifty per cent of the cases, the last tone of the second version was intonationally deviant either upwards or downwards. The subjects' task was to judge whether the last tone in the second version was an intonational deviant or not. Raw material from the research is presented in the form of psychometric functions. Tolerance zones of intonational deviations have been determined. The obtained results partially support the research findings on principles of tonal gravitation by other investigators, but some of the results are new.